When Caring for Perpetrators Becomes a Sentence: Recognizing Vicarious Trauma. (October 2015) - Munger, Tanya; Savage, Teresa; Panosky, Denise M.
Correctional health nurses are not exempt from vicarious traumatization, but this concept has yet to be explored. Correctional health nurses practice in environments that come with significant risk for traumatic exposure from inmates and coworkers. The Professional Quality of Life Scale was used as a proxy to measure vicarious trauma. Surveys were mailed to 2, 000 correctional health nurses that were on the mailing list of the National Commission on Correctional Health Care, with a total response rate of 10.1%. Respondents were asked to complete the Professional Quality of Life Scale and a short demographic survey. Findings reveal that vicarious traumatization does exist among correctional health nurses.